Sequence analysis of the ribosomal protein gene, RPS15 in cell line derived from human colorectal carcinoma - Yew, Keh Li (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Colorectal carcinoma (CRC) is a progressive cancer that is likely to be related with the changes in the gene expression in CRC due to sequence changes. In the recent finding on the human ribosomal protein gene, RPS15 has shown to be upregulated in nasopharyngeal carcinoma (NPC) and human hepatocellular carcinoma (HPC) tumor cells compared to the normal cells but no studies have been done in studying the RPS15 gene in CRC. The objective of this study is to carry out sequence analysis of RPS15 gene in CRC cell line, HCT116. The starting materials were the total RNA from HCT116 and transcribed into cDNA by using Moloney Murine Leukemia Virus Reverse Transcriptase (M-MLV RT). The cDNA was then successfully amplified by the polymerase chain reaction (PCR) and proceed with sequence analysis. The sequence of RPS15 from HCT116 showed high similarity of 99 % and conservation with the reference sequence of RPS15 at the National Centre for Bioinformatics (NCBI) website for both nucleotide and protein sequence. In addition, RPS15 gene encodes two biological significant sites, which are protein kinase C phosphorylation and N-myristoylation site. This finding suggests RPS15 gene is highly conserved in HCT116 and encodes for two biological important sites.